Toward Effective Mental Health Detection: Implementing Forward Chaining Method with DASS–21 - Nurul Hidayati, Novita; Arwin Dermawan, Dodik; Zul Fahmi, Hafizhuddin; Sri Sidhimantra, I Gde Agung; Putra Santoso, Rizky (Proceeding of International Joint Conference on UNESA, 2024)
Mental health is an important aspect of quality of life that is often overlooked. This study aims to design a website-based application called Serenity which is used to detect mental health conditions in the categories of depression, anxiety, and stress. This application utilizes the Depression Anxiety Stress Scale-21 (DASS-21) as a measurement tool and applies the Forward Chaining method to interpret the examination results. In the first stage, a needs analysis is carried out to determine the features to be developed in the application. After that, a system design was carried out that included designing an intuitive and easy-to-use user interface and user experience. The implementation process involves coding using PHP, CSS, Java Script, integration with MySQL databases, and system testing to ensure optimal functionality. The results showed that the Serenity application had an excellent performance with a score of 98% in the PageSpeed Insight test. The system was tested using black box testing which involved users showing results that met expectations and providing accurate results in detecting the user’s mental health condition.